A preliminary quantitative research on dividend policy and its impact on share prices - Xiao, Dezhi (2013)
This report is designed to find out the relationship between dividend policy and share price, generally, there are two camps theories within this area, one of them argues the dividend policy do not influence share value while the other one argues the dividend policy can affect share value via different approaches. Therefore, this report attempts to identify the relationship between dividend policy and share price via conducting an OLS analysis in 60 UK listed companies. Then, the result can be utilized as a new piece of evidence in modern capital market to demonstrate whether dividend policy has impacts on share price. After the data has been analyzed via OLS, the coefficient between dividend payout ratio and share price has been found and this coefficient suggests that there is no significant relationships between dividend policy and share price as the coefficient is quite small and insignificant. Hence, this result proves the dividend policy is irrelevant to share price in the current capital market as Miller and Modigliani (1961) proposed. Also, this report finds the earning per share (EPS) is strong positively related to share price, once again, this result proves M&M argument, the only factor which affects share price is company's earning ability not how it distributes its profit. In addition, for the practical implication, investors can use EPS as a decent filter in choosing shares to make their investment more profitable as the OLS model contains a relative high adjusted R square (about 70%) in explaining share prices and the EPS have a positive coefficient to share price within significant. Overall, this report finds out that the dividend policy do not affect share price, but the EPS is positively related to share price, and it can be a good explanatory factor in predicting share price.